Fingerprinting localisation with cruciate directional antennas for wireless sensor networks. (20th March 2014) - Jiang, Jehn–Ruey; Lin, Chih–Ming; Cheng, Kai–Chao; Huang, Shing–Tsaan
This paper proposes a novel fingerprinting localisation scheme, called fingerprinting localisation with cruciate directional antennas (FLCDA), using only one anchor node equipped with four directional antennas whose orientations are perpendicular to adjacent ones. The proposed FLCDA consists of two phases. In the RSSI gathering phase, a sensor node is placed at reference positions to send signals. And the RSSI values of the signals received by the four antennas are stored in the anchor node as the positions' fingerprints. In the localising phase, the anchor node localises a target sensor node by receiving its signals with the four directional antennas. The position associated with the fingerprint most matched with the received signals' RSSI values is assumed to be the target node's position. We also design and implement some techniques to accelerate FLCDA without affecting the accuracy too much. FLCDA and its variants are also compared with the related ones.